STRATEGI PEMASARAN DAGING AYAM BROILER RENDAH LEMAK DAN KOLESTEROL - N. E., Kurniawan; Putri, B. R. T.; Sukanata, I W. (Jurnal Peternakan Tropika, 2016)
The objective of this study was to analyze the internal and external factors, determine the attractiveness of the industry, and to recommend the effective strategies to market the products of broiler chicken meat low in fat and cholesterol. The study was conducted in Denpasar and Badung selected with purposive sampling, consumer respondents were selected by random sampling of 100 people and expert respondents were selected by purposive sampling totaling of 3 persons. The data used were quantitative and qualitative data, sourced from primary and secondary data. Methods of data collection were done by interviews, in-depth interviews, observation, and literature research. Data were analyzed by using IFE EFE matrix, IE matrix, SWOT analysis, and analysis of QSPM. The results showed that the total score of internal factor was 2.35, and the external factor was 3.11. The position of the product is in cell II. There are ten alternative strategies produced, namely: 1) making product differentiation, 2) conducting continuous promotion, 3) placing the SPG / SPB on the stand of products, 4) looking for distribution network, 5) making specific characteristic packaging, 6) obtaining product certification, 7) to be a supplier for restaurants, hotels and supermarkets, 8) standardizing the products, 9) cooperating with investors, and 10) building customer loyalty. The prioritized recommended strategy for marketing the products is by placing the SPG and SPB in the stand of products.
Keywords: marketing strategies, broiler chicken, fats, and cholesterol